2020
DOI: 10.1021/acs.jcim.0c00762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Force Fields for Intrinsically Disordered Proteins

Abstract: Molecular dynamics (MD) simulations of six upgraded empirical force fields were compared and evaluated with short peptides, intrinsically disordered proteins, and folded proteins using trajectories of 1, 1.5, 5, or 10 μs (five replicates of 200 ns, 300 ns, 1 μs, or 2 μs) for each system. Previous studies have shown that different force fields, water models, simulation methods, and parameters can affect simulation outcomes. Here, the MD simulations were done in an explicit solvent with RS-peptide, HEWL19, HIV-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 51 publications
10
40
1
Order By: Relevance
“…Despite, our REMD simulations result in slightly different helical abundancies for residues than the simulations conducted by Rahman et al. (2020) using the ff99IDPs and ff14IDPS parameters. Finally, we looked at the sequence‐based secondary structure propensity of Aβ 1‐40 using one of the most accurate methods for secondary structure prediction Jpred4.…”
Section: Resultscontrasting
confidence: 73%
“…Despite, our REMD simulations result in slightly different helical abundancies for residues than the simulations conducted by Rahman et al. (2020) using the ff99IDPs and ff14IDPS parameters. Finally, we looked at the sequence‐based secondary structure propensity of Aβ 1‐40 using one of the most accurate methods for secondary structure prediction Jpred4.…”
Section: Resultscontrasting
confidence: 73%
“…The initial monomolecular simulation for each peptide was conducted in a water box for 100 ns with a modified water model, TIP4P-D, and Amber99SB-ILDN forcefield. They can substantially reproduce the experimental observables for intrinsically disordered proteins and peptides [ 37 , 38 ]. The energy analysis demonstrated that each peptide monomer system was stable and validated, as seen in Supplementary Figure S5 .…”
Section: Resultsmentioning
confidence: 99%
“…Cloud architectures, such as the Google Compute Engine, are especially well suited to generate Markov state models, as the individual simulations can be run independently from one another, with no communication between machines required 35 . We chose the CHARMM22* over the CHARMM36m force field due to the better agreement with macroscopic observables such as radius of gyration for the closely related Aβ40 peptide 36,37 .…”
Section: Molecular Dynamics Simulations On the Google Compute Enginementioning
confidence: 99%